Endothelial basement membrane laminin 511 is essential for shear stress response. (9th December 2016) - Di Russo, Jacopo; Luik, Anna‐Liisa; Yousif, Lema; Budny, Sigmund; Oberleithner, Hans; Hofschröer, Verena; Klingauf, Juergen; van Bavel, Ed; Bakker, Erik NTP; Hellstrand, Per; Bhattachariya, Anirban; Albinsson, Sebastian; et al.
Abstract: Shear detection and mechanotransduction by arterial endothelium requires junctional complexes containing PECAM‐1 and VE‐cadherin, as well as firm anchorage to the underlying basement membrane. While considerable information is available for junctional complexes in these processes, gained largely from in vitro studies, little is known about the contribution of the endothelial basement membrane. Using resistance artery explants, we show that the integral endothelial basement membrane component, laminin 511 (laminin α5), is central to shear detection and mechanotransduction and its elimination at this site results in ablation of dilation in response to increased shear stress. Loss of endothelial laminin 511 correlates with reduced cortical stiffness of arterial endothelium in vivo, smaller integrin β1‐positive/vinculin‐positive focal adhesions, and reduced junctional association of actin–myosin II. In vitro assays reveal that β1 integrin‐mediated interaction with laminin 511 results in high strengths of adhesion, which promotes p120 catenin association with VE‐cadherin, stabilizing it at cell junctions and increasing cell–cell adhesion strength. This highlights the importance of endothelial laminin 511 in shear response in the physiologically relevant context of resistance arteries. Synopsis: Laminin 511 (Laminin α5) is required for adhesion of endothelial cells to their basement membrane and stabilizes junctional VE‐cadherin, and this is required for the shear stress response of resistance arteries. Laminin 511 is crucial for physiological endothelial cell shear stress‐induced arterial vasodilation. Integrin β1‐mediated adhesion of arterial endothelial cells to laminin 511 stabilizes VE‐cadherin at adherens junctions. Laminin 511 regulates endothelial cell actin cortical tension in vivo . Abstract : Laminin 511 (Laminin α5) is required for adhesion of endothelial cells to their basement membrane and stabilizes junctional VE‐cadherin, and this is required for the shear stress response of resistance arteries.